2020
DOI: 10.1080/08897077.2019.1671937
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for Using Electronic Cigarettes in Young Adults: A Systematic Review

Abstract: Background: The most common reasons why adults use e-cigarettes are to stop or reduce tobacco smoking. However, it is unclear if this reason is evenly distributed between young and older adults. Objectives: describe the motivations for e-cigarette use amongst young adults aged 18–25 and compare the reasons for using e-cigarettes of people who currently or formerly used tobacco products to those who had never smoked tobacco prior e-cigarette use. Methods: PubMed®, Scopus®, Cochrane Library®, SocINDEX®, PsycART… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 58 publications
(108 reference statements)
2
32
0
1
Order By: Relevance
“…The reasons for using EC in young adults are varied and are not limited to stopping smoking. Quit smoking is not the only reason to use EC by young adults [31].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for using EC in young adults are varied and are not limited to stopping smoking. Quit smoking is not the only reason to use EC by young adults [31].…”
Section: Discussionmentioning
confidence: 99%
“…A scoping review of the literature was conducted to identify various empirically supported influences on e-cigarette uptake among youth, which was then used to develop the coding framework to analyze influences present in vaping ads. The search strategy was developed by the research team, including a research librarian and experts in youth vaping and substance use, and based on a methodology reported by Kinouani and colleagues [ 29 ]. The scoping review used two databases, Medline on the OVID platform and CINAHL on the EBSCO platform, using a combination of keywords and database-specific subject headings.…”
Section: Methodsmentioning
confidence: 99%
“…In comparison, a German study found that the vast majority of German youth (aged 14–19) cited curiosity (73.1%) as their reason for EC use, followed by quitting tobacco use (14.9%) and as a complement to tobacco use (7.5%) [ 23 ]. In a systematic review of six studies among young adults in varied settings (i.e., USA, Romania, France, New Zealand, and Saudi Arabia), curiosity and EC use by friends were the primary reasons for EC initiation among non-smokers [ 24 ]. Among former and current CC users, ECs were used due to perceptions of harm reduction, to aid smoking cessation, to use in smoking-restricted areas, for lower cost compared to CCs, or for flavoring [ 24 ].…”
Section: Why Do Youth Vape?mentioning
confidence: 99%